Circadian expression of the dnaK gene in the cyanobacterium Synechocystis sp. strain PCC 6803. - Aoki, S (1995)
The expression of the dnaK gene in the cyanobacterium Synechocystis sp. strain PCC 6803 was continuously monitored as bioluminescence by an automated monitoring system, using the bacterial luciferase genes (luxAB) of Vibrio harveyi as a reporter of promoter activity. A dnaK-reporting bioluminescent Synechocystis strain was constructed by fusing a promoterless segment of the luxAB gene set downstream of the promoter region of the Synechocystis dnaK gene and introduction of this gene fusion into a BglII site downstream of the ndhB gene in the Synechocystis chromosome. Bioluminescence from this strain was continuously monitored and oscillated with a period of about 22 h for at least 5 days in continuous light. The phase of the rhythm was reset by the timing of the 12-h dark period administered prior to the continuous light. The period of the rhythm was temperature compensated between 25 and 35 degrees C. Thus, the bioluminescence rhythm satisfied the three criteria of circadian rhythms. Furthermore, the abundance of dnaK mRNA also oscillated with a period of about 1 day for at least 2 days in continuous light conditions, indicating circadian control of dnaK gene expression in Synechocystis sp. strain PCC 6803.